Construction of Underground Gas Storages Facilities, Injection and Extraction of Gas during Exploration-Industry Operation - Aliyeva, O.A.; Аliyev А.S. (Herald of Azerbaijan Engineering Academy, 2021)
The article analyzes the data on the creation of North Caucasus underground gas storage facilities (UGS) in 1960-1971 and the injection and production of gas into storage facilities during exploration and industrial operation. The followings have been obtained as a result of the analysis. Increased gas injection and extraction from gas storage facilities in the former USSR; change in the absolute value of gas over time, while it is pumping into storage, taking out and its rising; a decrease in the volume ratio of gas injection and extraction over time. Compression of water with gas is not very large. Therefore, it is hardened as follows. Under formation conditions, gas has a lower density than water, i.e. it is light and its viscosity is less than water, gas has a large mobility. In underground gas storages (UGS), gas is divided into active and buffer. The part of the gas that is extracted from the storage is called the active part (when the demand for gas decreases in the summer). Buffer gas refers to the part that is constantly in underground gas storage (UGS). It provides pressure in the reservoir and is sufficient to supply active gas to the production wells. The maximum and minimum pressures are obtained in underground gas storages (UGS-s) where the share of buffer gas is very high. The volume of active and buffer gas in underground gas storages (UGS) depends on its geometric dimensions, shape, depth of deposition, porosity, rock permeability, minimum and maximum pressure in the annulus, gas injection and extraction technologies.